2007
DOI: 10.21098/bemp.v8i4.148
|View full text |Cite
|
Sign up to set email alerts
|

Fungsi Intermediasi Dalam Efisiensi Perbankan Di Indonesia: Derivasi Fungsi Profit

Abstract: This paper analyze the bank efficiency in Indonesia by deriving the profit function. We apply the stocahstic frontier approach on monthly data during 2001:01 – 2004: 12, covering the 20 largest asset banks. We incorporate the function of the bank as an intermediary institution by including the intermediary stressing variable on the profit function. This is important to capture the possibility when the large profit is gathered from non-operational profit sources such as recap fund or SBI.The result of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Creating good economic stability requires a healthy, effective, and efficient banking system. Otherwise, bank credit will not be allocated appropriately, so the bank's credit portfolio cannot encourage overall economic growth [4]. Therefore, the banking industry must run in a healthy, stable, and efficient manner to create a more equitable and sustainable economic growth [5].…”
Section: Introductionmentioning
confidence: 99%
“…Creating good economic stability requires a healthy, effective, and efficient banking system. Otherwise, bank credit will not be allocated appropriately, so the bank's credit portfolio cannot encourage overall economic growth [4]. Therefore, the banking industry must run in a healthy, stable, and efficient manner to create a more equitable and sustainable economic growth [5].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the Islamic banking industry has developed to unprecedented proportions. The growing number of Islamic banks has compelled the Indonesian banking sector to improve its competitiveness by outperforming and outperforming the Islamic banking market (Astiyah, 2006;Endri, Ritha, H, Hadiyati, 2010;Hadad, 2003) The banking industry has the potential to contribute to the accomplishment of Sustainable Development Goals (SDGs), particularly in terms of ensuring community equity. The banking industry is a sharia-compliant financial institution that will contribute to the growth of the real sector, particularly in productive economic activities, but has not yet accounted for a significant amount of funding for productive activities.…”
Section: Introductionmentioning
confidence: 99%
“…Bank efficiency is an important indicator to analyze the performance of a bank (Girardone et al, 2004). Astiyah and Husman (2006), claims that bank efficiency is not only important as an indicator in banking but also as a means to further enhance the effectiveness of monetary policy so that it can more effectively reach its target. Bank efficiency in Indonesia has been strongly emphasized after the period of the enactment of the ASEAN Economic Community (MEA), during which Bank Indonesia (BI) issued Bank Indonesia Peraturan Bank Indonesia Nomor 14/26/2012 (Regulation Number 14/26/PBI/2012) concerning Business Activities and Office Networks Based on Bank Core Capital.…”
Section: Introductionmentioning
confidence: 99%
“…Banking efficiency has attracted the interest of multiple researchers with various approaches. Among them, Astiyah and Husman (2006) examined the efficiency level of 20 banks with the largest assets in Indonesia using the stochastic frontier analysis method. The results of their research demonstrated that banks from foreign bank groups tend to be more efficient.…”
Section: Introductionmentioning
confidence: 99%